2011
DOI: 10.4021/gr357w
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Gastric Intestinal Metaplasia by Mottled Patchy Erythema Seen on Endoscopy

Abstract: BackgroundIntestinal metaplasia (IM) is regarded as a premalignant lesion. However, endoscopic diagnosis of IM has been considered difficult. Using endoscopy, we found a unique pattern of erythema, “Mottled Patchy Erythema (MPE),” which includes severe IM. Helicobacter pylori (Hp) infection itself can cause erythema, which reflects histologic changes in the gastric mucosa. Therefore we enrolled Hp eradication patients to validate the relation between MPE and pathologic findings.MethodsWe enrolled patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…Atrophic change, occurring as a result of H. pylori infection, is thought to remain after eradication therapy [26] . Moreover, in our previous study, MPE, which is recognized as a flat or slightly depressed reddish lesion that is distinguishable from the congested mucosa, emerged after H. pylori eradication therapy [12] . In the study too, atrophic change and MPE was highly predictive of H. pylori eradicated mucosa, suggesting that a combination of these findings is highly valuable in clinical practice.…”
Section: Diagnostic Odds Ratio Of Endoscopic Findingsmentioning
confidence: 85%
See 2 more Smart Citations
“…Atrophic change, occurring as a result of H. pylori infection, is thought to remain after eradication therapy [26] . Moreover, in our previous study, MPE, which is recognized as a flat or slightly depressed reddish lesion that is distinguishable from the congested mucosa, emerged after H. pylori eradication therapy [12] . In the study too, atrophic change and MPE was highly predictive of H. pylori eradicated mucosa, suggesting that a combination of these findings is highly valuable in clinical practice.…”
Section: Diagnostic Odds Ratio Of Endoscopic Findingsmentioning
confidence: 85%
“…The presence or absence of the following 11 distinctive endoscopic findings were evaluated (Figures 1 and 2): regular arrangement of collecting venules (RAC) [5] , linear erythema [9] , hemorrhage [9] , fundic gland polyp (FGP) [10] , atrophic change [6,7] , severity of atrophy (open/ closed) [6,7] , rugal hyperplasia [8] , edema [9] (which is visible as a thickened mucosal layer especially at the angulus and cardia), spotty erythema [9] , exudate [9] , xanthoma [11] , and mottled patchy erythema (MPE) [12] . A well-experienced endoscopist (Kobayakawa M) assessed the findings, and to determine inter-observer agreement, another experi- …”
Section: Endoscopic Findings Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagata et al [9] have demonstrated that mottled patch erythema, which may include RDLs, is a response to intestinal metaplasia. In the present study, we demonstrated that a variety of magnifying patterns were found in association with RDLs, and the histopathological features of RDLs were not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Nagata et al [9] reported that endoscopic findings of mottled patchy erythema were characteristic of pathological intestinal metaplasia in patients who have received eradication therapy. In addition, Moribata et al [10] report that the presence of map-like redness observed after H. pylori eradication is a useful endoscopic marker to predict a diagnosis of metachronous gastric cancer following endoscopic submucosal dissection [10].…”
Section: Introductionmentioning
confidence: 99%